Analisis Peran Media Sosial terhadap Peningkatan Pemesanan oleh Pelanggan. Studi Kasus: Reddoorz - Desika Nadia Putri; Muhammad Bhirawa Dwi Atma Citalada (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This study analyzes the role of social media in increasing customer bookings through digital marketing strategies for RedDoorz student interns. Social media is used as the primary means of implementing digital marketing strategies to reach a wider range of potential customers. The research method used is a quantitative approach with data collection techniques through questionnaires distributed to respondents. The independent variable (X) is the digital marketing strategy with indicators of content quality, information credibility, and promotional visuals, while the dependent variable (Y) is customer decisions with indicators of purchase interest, booking intensity, and order conversion. Primary data were collected through questionnaires from student interns. The independent variable in this study is the digital marketing strategy measured through indicators of content quality, information credibility, and promotional visuals. Meanwhile, the dependent variable is customer decisions measured through customer purchase interest, booking intensity, and order conversion. The data obtained were analyzed to determine the effect of digital marketing strategies through social media on customer decisions in making bookings. The results of this study are expected to provide an overview of the effectiveness of social media as a digital marketing tool and become evaluation material for RedDoorz in improving its social media-based marketing strategy.